Optimalisasi Pengelolaan Paten Melalui Lokapasar: Formulasi Pengaturan Paten Dalam Bentuk NFT di Indonesia - Zaki Priambudi; Sendy Pratama Firdaus; Natasha Intania Sabila; Nuzulia Kumala Sari (Badan Strategi Kebijakan Hukum, 2023)
This research seeks to examine a Patent regulation in the form of a Non-Fungible Token (NFT-Patent) in Indonesia. The implementation of NFT-Patent is intended to overcome the problems of patent management in Indonesia, such as the long and expensive bureaucratic process of patent, the absence of an integrated patent commercialization ecosystem, and the existence of a legal vacuum regarding the valuation mechanism of a patent. This research aims to answer a formulation of the problem related to how the model of NFT-Patent regulation through the online marketplace in Indonesia. The analysis of the problem formulation will start by comparing Non-Fungible Token (NFT) regulations in Indonesia with other countries, followed by conceptualizing the transfer of ownership rights from NFT-Patent carried out through an online marketplace, then end by formulating the regulation of the NFT-Patent online marketplace in the statutory regulations in Indonesia. By combining doctrinal research methods and reform-oriented research, this study found that based on Indonesia's positive law, NFT is categorized as a crypto commodity which is an object of tax and BKP. On the contrary, the United States sees NFT as conventional IPR in digital form for tax purposes. NFT-Patent is categorized as an intangible movable object whose transaction is considered valid as long as it meets the provisions of Article 1320 of the Civil Code and Article 46 paragraph (2) of the Government Regulation Number 71 of 2019 concerning the Implementation of Electronic Systems. In its implementation, a transition process is carried out with several stages. The transition stages are regulated in the Regulation of the Minister of Law and Human Rights with the Directorate General of Intellectual Property as the manager. If most of the transition process has been running, the government needs to update the 2016 Patent Law by implementing the Separation Principle by separating the purpose of using inventions into 3, namely consumption, production, and innovation. Ultimately, this research recommends the government to regulate NFT specifically, synergize with blockchain-based Patent ecosystem development companies and encourage collaboration between universities and industrial companies in developing Patents.